CONSUMER WILLINGNESS TO PAY FOR TENNESSEE CERTIFIED BEEF. (12th March 2018) - MERRITT, MEAGAN G.; DELONG, KAREN LEWIS; GRIFFITH, ANDREW P.; JENSEN, KIMBERLY L.
Abstract: Although Tennessee has Advanced Master Beef Producer (AMBP) and Beef Quality Assurance (BQA) certifications for cattle producers, currently there is no state-certified beef labeling program. A choice experiment was administered to Tennessee consumers to determine their willingness to pay for Tennessee Certified Beef (TCB) and other attributes such as labels indicating producer participation in AMBP and BQA. Random parameter logit model results indicate consumers most valued TCB steak and no-hormones-administered ground beef. Consumers also valued many labels when appearing alongside the TCB label. The impact of providing participants label definitions prior to the choice experiment was examined.